Infografis Prakiraan Cuaca di Provinsi Papua Tengah dengan Menggunakan QGIS & Adobe Photoshop - Usman Arfan; Donny Irwanto; Kristia Yuliawan (STMIK Pesat Nabire, 2024)
Central Papua Province is a new autonomous region province located in the Papua region. consists of 8 districts with the dominant topography of high rainfall for most of the year. As a result, the region in Central Papua often experiences hydrometeorological disasters, including floods, landslides, fallen trees, collapsed roofs. This study aims to map weather forecast infographics in Central Papua Province with QGIS and Adobe Photoshop Using the utilization model in the QGIS application which is overlaid with shapefile data from the BMKG signature of Central Papua Province. As well as shapefile data from the geospatial Indonesia website, namely the latest village and administrative boundaries 2022/2023 for the expansion of 38 provinces on a scale of 10K BIG. Then On the photoshop application helps infographic image editing. In making a map of Central Papua province with additional administrative boundaries of protected areas, tourist sites and latitude and longitude. As well as BMKG signature polygon alerts from signature.bmkg.go.id/ site. Once overlayed, it produces any area affected.